Perancangan dan Implementasi Alat Pengusir Hama Burung Berbasis Sistem Audio Menggunakan DFPlayer Mini dan Amplifier PAM8403 pada Area Pertanian - Sujono Sujono; Rangga Adi Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Bird pests are one of the main causes of reduced crop yields, particularly during the seed formation to ripening stages. Conventional bird deterrent methods, such as scarecrows, reflective tape, and manual monitoring, tend to lose their effectiveness because birds are able to adapt to static stimuli. This study aims to design and implement a low-cost audio-based bird deterrent device. The developed system uses the DFPlayer Mini as an audio player and the PAM8403 amplifier as a power amplifier to drive an external speaker, thereby covering a wider area. This system is controlled by a microcontroller that randomly controls sound playback, both in terms of timing and audio type, to reduce bird habituation. The DFPlayer Mini supports FAT16/FAT32 storage and audio file management, while the PAM8403 is a Class-D amplifier with an output power of up to approximately 3 watts. Testing included functional verification, sound pressure level (SPL) measurements, and power consumption estimates. The results showed that the system operates stably and is capable of producing sound with sufficient intensity to deter birds. The random playback pattern proved more effective than continuous playback. Thus, this device has the potential to be an efficient and environmentally friendly alternative solution for bird pest control.